Renin-secreting chromophobe renal cell carcinoma: An uncommon cause of secondary hypertension in a young female - Tareq Jarrar; Younes Jafar Hamam; Hadeel Abdallah Al Kayed; Bassel Esmat Alrabadi; Ayham Kamel Milhem; Maryam Hisham Alqatawna; Husam Odaibat (Urology Case Reports)
Renal cell carcinoma (RCC) is a rare but significant cause of secondary hypertension. Chromophobe RCC represents 5 % of all RCC cases, with renin secretion being even rarer. We report a case of a 32-year-old female with six-month history of uncontrolled hypertension. Laboratory findings showed elevated plasma renin and aldosterone levels. Imaging revealed a large left renal mass. After radical nephrectomy, histopathology confirmed chromophobe RCC. Her blood pressure normalized postoperatively, and she was normotensive at 1-month follow-up. This case underscores the importance of considering renal tumors in hypertensive patients and the role of surgery in achieving favorable outcomes.